Wireless electric energy transmission system and its recording system using PZEM004T and NRF24L01 module - Markus Dwiyanto Tobi; Vina N. Van Harling (Institute of Advanced Engineering and Science, 2021)
Electrical energy can not be separated from the name kWh Meter, a tool used to measure and record the amount of electrical energy usage has a shortage of kWh meters can not be monitored remotely how much energy is used, so it is rather inconvenient for PLN officials to check the use of electricity for postpaid customers. This research was conducted to design a prototype of a wireless electrical energy transmission system and design a wireless electrical energy recording system using the NRF24L01 wireless transmitter module and the PZEM004T kWh meter module. The design in this study uses the principle of electromagnetic induction to transfer electrical energy at close range, while to transmit data, the authors use the NRF24L01 module. Besides, the authors use the PZEM004T module to measure various magnitudes. Based on the results of observations and measurements of the design of the tool, the authors found that the transmission of electrical energy using electromagnetic induction is not effective for longer distances because the energy lost in the air is getting bigger. So this technology needs to be further investigated. Besides, the measurement of electrical quantities using the PZEM module has a small difference (under 2%) with measurements using a multimeter, so it can be said that the measurement with the PZEM004T module is effective.